SIMULATION OF RAIL DIRECTIONS WORK - Kozachenko, D. M.; Mozolevych, H. Ya.; Vlasiuk, O. V. (Science and Transport Progress, 2009)
The computer-aided simulation model is offered that can be used for the research of the railway traffic organization and also for the estimation of influence of the train parameters on the operation indices of railway lines and directions.